Social workers in the first decade of the 21st cetury. 40 years after Jesús María Vázquez’ publicacion Status of social services in Spain - Gómez García, Rogelio (Cuadernos de Trabajo Social, 2012)
Coinciding with the 40th anniversary of the first sociological study on social work in our country, titled «Status of Social Services in Spain» by Jesús María Vázquez (1971), this article presents some of the main changes that have occurred in our profession in the last four decades.
Keywords: trabajo social; profesión; profesionalización; trabajadores sociales